Foreign Bodies in the Urinary Bladder! A Single-Center Experience in Endoscopic Management (Medical Forum Monthly, 2023)
Objective: This study was conducted to characterize the nature of foreign bodies, presentations, modes of insertion, diagnosis, and their management modalities.Study Design: Observational / analytical studyPlace and Duration of Study: This study was conducted at the Department of Urology, D.G. Khan Medical College, Dera Ghazi Khan from January 2018 to September 2022.Materials and Methods: 41 patients with foreign bodies in their urinary bladder were treated at our centre. The records of these patients were reviewed and analysed for their symptoms, mode of insertion, diagnosis, and management.Results: A total of 41 foreign bodies were recovered from the urinary bladders during the study period. These included Ribbon gauze, foleys balloon with stones, jj stents, contraceptive devices, prolene stitches with hanging stones, candle, wooden pieces, hairpin and electric wire. The common presenting features were painful micturition and suprapubic pain. The diagnosis was established radiologically in most of the cases. The circumstances of insertion were variable; iatrogenic in 35(85.36 percent) cases, sexual stimulation in 4 (9.75 percent), and physical torture in one (2.0 percent). 39 (95.12 percent) foreign bodies were recovered endoscopically, and cystolithotomy was required in 2 (4.87 percent) patients.Conclusion: Endoscopic retrieval is an excellent management modality for the treatment of foreign body in urinary bladder, being a rare instance of foreign body in urinary bladder usually it’s diagnosis is overlooked but patients not responding to adequate medical treatment for LUTS, should be suspected for foreign body in urinary bladder